A new indicator of inflation expectations anchoring - Filippo Natoli; Laura Sigalotti (European Central Bank (ECB), 2017)
We compare the degree of anchoring of inflation expectations in the euro area, the United States and the United Kingdom, focusing on the post-crisis period. First of all, we estimate a set of measures of average and tail correlation using inflation swaps and options, following Natoli and Sigalotti (2016). To quantify the degree of anchoring, we also propose a new indicator based on the results of a logistic regression, measuring the odds that strong negative shocks to short-term expectations are channelled to large declines in long-term expectations. The results reveal, for the euro area, an increase in the de-anchoring risk during the last quarter of 2014; while showing a significant reduction after the peak, our de-anchoring indicator remains high and volatile in 2015 and 2016. Expectations in the US and UK are instead found to be firmly anchored.
Keywords: C14; C58; E31; E44; G13; 330; anchoring; inflation expectations; inflation options; inflation swaps; option-implied density; tail co-movement